Neurosurgery for Chronic Neuropathic Pain - Jung Y Park; Andres M Lozano (Pain Research and Management)
Neurosurgery can play a role in the management of patients with refractory chronic neuropathic pain. However, selecting patients as candidates for surgery and choosing the most appropriate surgical procedure is challenging, and surgical interventions often have limited efficacy. When considering surgery, neuroaugmentative or neuromodulative procedures (eg, peripheral, spinal, motor cortex or deep brain stimulation) are generally preferred over ablative procedures as initial modalities. With better understanding of specific pain mechanisms, surgery will have more to offer patients with chronic neuropathic pain.